Measuring Parent Satisfaction With Care in Neonatal Intensive Care Units: The EMPATHIC-NICU-USA Questionnaire - Lake, Eileen T.; Smith, Jessica G.; Staiger, Douglas O.; Schoenauer, Kathryn M.; Rogowski, Jeannette A. (Frontiers in Pediatrics, 2020)
Background: Neonatal intensive care unit (NICU) patient satisfaction is measured as parent satisfaction. Parents are critical to the family-centered care model and can evaluate care. Several EMPATHIC instruments were developed in the Netherlands to measure parent satisfaction with neonatal and pediatric intensive care. EMPATHIC instruments comprise five domains: information, care and treatment, organization, parental participation, professional attitude, and a total score. To our knowledge, the EMPATHIC has not been adapted for USA use. Objectives: 1) To select a relevant EMPATHIC instrument for our study. 2) To expand the content reflecting the role of nurses and the cultural heterogeneity of USA NICU infants. 3) To adapt the selected EMPATHIC instrument to USA English. 4) To establish psychometric properties of the linguistically-adapted instrument. 5) To evaluate instrument performance with additional items. Methods: The EMPATHIC-30 was selected based on shortest length, high overlap with neonatal EMPATHIC-N, and availability of a validated Spanish-language version. Six items from the EMPATHIC-N were added, two of which were split into separate items, resulting in the EMPATHIC-38. A neonatal nurse practitioner adapted wording to USA English. Cognitive debriefing was performed with eight NICU parents to evaluate adapted wording. Parent survey data from a study about missed nursing care and NICU parent satisfaction were utilized. Internal consistency of the five domains and overall score was measured by Cronbach’s alpha. Spearman’s rank correlations were computed for domains and overall score with four validity measures. Differential validity was determined using thirteen parent demographic subgroups. Results: Data were from 282 parents. Parent race was predominantly White (61%) or Black (22%). One fifth were Hispanic. The adapted wording was satisfactory. Four of the five EMPATHIC-30 and EMPATHIC-38 domains had Cronbach alphas at or above .70, indicating acceptable reliability. Correlations between the domain, total scores, and validity indicators ranged from .30 to .57, indicating positive, moderate associations. Results were replicated in demographic subgroups. Reliability and validity of the three domains with additional items were better than or equivalent to values for the original. Conclusion: The linguistically adapted EMPATHIC-30-NICU-USA and the expanded EMPATHIC-38-NICU-USA exhibit satisfactory psychometric properties and are suitable for use in USA NICUs.